Truth and Error of Conscience According to the Magisterium of the Church - Josef Spindelböck (Polonia Sacra)
The relation of truth and error in conscience according to the newer actual Magisterium of the Church is the theme of this article, following a hermeneutic of reform in continuity (Benedict XVI). Emphasis is given first on Veritatis splendor by Pope John Paul II, then on Humanae vitae by Pope Paul VI and finally, in a special way, to Amoris laetitia by Pope Francis. A focus is laid on the dimension of virtue education since this helps the persons involved not only to grasp the truth of relevant moral values but also to realise morally good acts with the help of Divine grace. Even in situations of personal limitation, there is always a light of God telling the person how to know and do the good.